2021
DOI: 10.3389/fphar.2021.713331
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BCL9 Modulates the Cellular Landscape of Tumor-Associated Macrophages in the Tumor Immune Microenvironment of Colorectal Cancer

Abstract: Tumor-associated macrophages (TAMs) are an indispensable part of the tumor microenvironment (TME), and they likely play a negative rather than positive role in cancer treatment. However, the cellular landscape and transcriptional profile regulation of TAMs in the case of tumor gene inactivation or chemical interference remains unclear. The B-cell lymphoma 9/B-cell lymphoma 9-like (BCL9/BCL9L) is a critical transcription co-factor of β-catenin. Suppression of Bcl9 inhibits tumor growth in mouse models of colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…This suggests that the imbalance in M0 macrophages and dendritic cells in the high-risk group may reduce the survival of patients. Previous articles have shown that cancer cells can cooperate with macrophages to promote proliferation, migration, invasion, angiogenesis, and metastasis, which are all consistent with our findings ( Huang et al, 2018 ; Wei et al, 2021 ; Xiao et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that the imbalance in M0 macrophages and dendritic cells in the high-risk group may reduce the survival of patients. Previous articles have shown that cancer cells can cooperate with macrophages to promote proliferation, migration, invasion, angiogenesis, and metastasis, which are all consistent with our findings ( Huang et al, 2018 ; Wei et al, 2021 ; Xiao et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Using identical mice xenograft models, a group of scientists from China described that BCL9 inhibition attenuated CRC growth via inhibiting TAM polarization from M0 to M2 phenotype that interfered with inflammatory actions of M0 and M1 TAMs. Based on the cellular landscape and transcription differences of TAMs after BCL9 suppression, they demonstrated that regulation of Wnt signalling via BCL9 suppression was expected to impair TAM-induced inflammation, CRC progression and immune surveillance ( 60 ). In a nutshell, unlike traditional immunotherapy, which targets solely CRC patients in late stages with MSI-H, scRNA-seq immune transcriptional studies offer an alternative option for precision medicine by targeting the Wnt signalling pathway via BCL9 depletion.…”
Section: Remodelling Of Time Via Nuclear B-cell Ly...mentioning
confidence: 99%
“…Tumour-associated macrophages (TAMs) are critical in the establishment of the TIME through their production of cytokines and chemokines, representing the most abundant immune cell population infiltrating colorectal tumors ( 59 , 60 ). A detrimental effect on cancer treatment is more likely with TAMs than a beneficial effect since they are known to promote tumor angiogenesis, growth, metastasis (via miRNA-containing exosome secretion, matrix metalloproteinase 9 expression, epithelial-to-mesenchymal transition) and immunosuppression ( 61 , 62 ).…”
Section: Tumour-associated Macrophage Is the Second Significant Key C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive analysis of the non-epithelial scRNA-seq data derived from precancerous lesions and CRC revealed that the proportion of CD8 + T cells, natural killer cells, and γδT cells (labeled cytotoxic cells) was significantly increased in serrated polyps compared to that in adenomas ( 54 ). Another study examined TAMs in CRC and found that Bcl9 deficiency caused macrophage polarization inhibition from M0 to M2 and altered the CRC tumor microenvironment to further interfere with the inflammation of M0 and M1, the cell type balance and transcription differences in TAMs regulated by BCL9-driven Wnt signaling affected immune surveillance and inflammation in cancer ( 55 ). Together, with the support of new technologies, SCS has greatly promoted a thorough understanding of the tumor microenvironment.…”
Section: Scs Applications and Achievements In Crcmentioning
confidence: 99%